(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Extubation is associated with significant hemodynamic stress responses due to sympathetic stimulation, which may be harmful in susceptible patients. Magnesium sulfate, owing to its vasodilatory and sympatholytic properties, may attenuate these responses. Aim: To evaluate the effectiveness of intravenous magnesium sulfate in attenuating hemodynamic responses during extubation. Methods: This prospective, randomized comparative study was conducted on 60 patients (ASA I–II), aged 20–50 years, undergoing extubation in emergency medicine department and critical acre icu at Sree Mookambika College of Medical Sciences. Patients were divided into two groups: Group A received magnesium sulfate (30 mg/kg in 100 ml normal saline), and Group B received 100 ml normal saline. Hemodynamic parameters including heart rate, systolic blood pressure, diastolic blood pressure, and mean arterial pressure were recorded at baseline, during extubation, and up to 15 minutes post-extubation. Extubation quality, sedation score, and adverse effects were also assessed. Results: Baseline demographic characteristics were comparable between the groups (p>0.05). From 2 minutes onwards and up to 15 minutes post-extubation, heart rate and blood pressure parameters (SBP, DBP, MAP) were significantly lower in the magnesium sulfate group compared to the control group (p<0.05). Extubation quality was better in Group A, with 83.3% of patients having favorable scores compared to 33.3% in Group B (p<0.05). Sedation scores were higher in the control group, while adverse effects were minimal and comparable between groups. Conclusion: Magnesium sulfate at a dose of 30 mg/kg effectively attenuates hemodynamic responses to extubation, improves extubation quality, and has a favorable safety profile, making it a useful adjunct in anesthetic practice.